Introducing Dreams of Dali in a Tertiary Education ESP Course: Technological and Pedagogical Implementations - Christoforou, Maria; Efthimiou, Fotini (My University, 2023)
Technology-enhanced teaching and learning environments transform the learning experience and increase student interest and engagement in the lesson. Virtual Reality (VR) has been identified as a multimodal medium that offers highly interactive and fully immersive experiences through which students can access a variety of meanings and enter a new social learning space which transcends classroom boundaries. VR also constitutes an innovative digital tool for foreign language (FL) learning in tertiary education through which teachers can promote a more situated learning context. Based on the multimodal affordances of the VR application Dreams of Dali, this paper aims to propose meaningful ways the application can be embedded in an English-for-Specific-Purposes (ESP) course in tertiary education, foregrounding the delivery of pedagogical content, creating student immersive literacy practices, and leading to alternative ways of conceptualising meanings. The immersive environment in Dreams of Dali can pose an instructional design tool which can increase familiarisation with course-related content in English for Fine Arts and help simulate an authentic surrealistic environment that deviates from static art-related images and passive surrealist representations of the art movement in the classroom.
Keywords: Virtual Reality-Enhanced Language Learning; Dreams of Dali; English for Specific Purposes (ESP)